Transcatheter closure of patent ductus arteriosus in infants weighing less than 6 kilograms – a two-center experience. Technical considerations - Michał Gałeczka; Michał Kapałka; Maciej Chojnicki; Michał Krawiec; Filip Tyc; Roland Fiszer (Cardiology Journal)
BACKGROUND: Transcatheter closure has become the method of choice for treating patent ductus arteriosus (PDA) in a majority of patients. The only approved device for treating infants weighing less than 6 kilograms is the Amplatzer Piccolo Occluder (APO). The aim of this study is to summarize the experience of two centers in performing transcatheter PDA closure in infants weighing less than 6 kilograms. METHODS: Retrospective, descriptive, and nonrandomized analysis included all 45 infants weighing less than 6 kg who underwent transcatheter PDA closure between 2013 and 2023 at two tertiary centers, following the introduction of APO. Medical records, procedural outcomes, and one-month follow-up were analyzed. Applied devices were: APO in 37 (of whom 3 were off-label due to PDA size), Amplatzer Duct Occluder I (ADO) in 3, and Amplatzer Vascular Plug II (AVP) in 5 cases. RESULTS: The overall success rate was 97.8%. There were 2 major complications (4.4%), including one device protrusion. A residual shunt was noted in one patient 24 hours after the procedure, but none were observed after one month. Off-label devices were implanted in insignificantly larger and longer PDAs. There were no significant differences between the labeled and off-label groups in terms of procedural success, major complications, or residual shunts. CONCLUSIONS: APO is a safe and effective device to treat PDA in infants weighing less than 6 kilograms, however, off-label devices are needed in a considerable number of patients. Proper use of off-label devices yields comparable to APO results.